Awareness about Advantages and Disadvantages of Abdominoplasty in the Kingdom of Saudi Arabia - Madiha R. Mahmoud, Farah Khalid F Alturki, Abdulwahab Hatim M Alshammari, Maram Mubarak N Aldhferi, Nada Mohammad M Omar, Shuruq Obaid Alshammari, Zainab Eisa J Alobaidi, Moath Saleh S Alzahrani, Sherif Gad Abdelaziz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Abdominoplasty (AP) is a pervasive procedure in cosmetic clinics with spectrum cosmetic reasons used globally under the giant umbrella of enhancing the quality of life. In Saudi Arabia (KSA), AP is the most common requested body-contouring surgery. It is associated with a significant number of complications, thus, there is a need to increase the clinical knowledge of physicians about AP to increase their clinical management ability of these patients as well raise the awareness of potential patients. Aim of study: The study aims to increase the awareness about advantages and disadvantages of AP among Saudi physicians and patients going to have an AP surgery. Methodology: The study adopts a quantitative descriptive approach among public and private cosmetic clinics practicing AP surgery. An online questionnaire form was distributed to patients who had AP surgery. Results: total of 229 patients participated in this study, 172 (75.1%) males and 57 (24.9%) females. One third of participants with BMI >30. The main reasons of performing AP surgery were cosmetics (96.9%), weight loss (86.9%), sagging skin (67.2%) and stretch marks (42.8%). only 12.2% need to re-correct their primary operations and majority (89.9 %%) reported a positive response of AP satisfaction, weight loss (67.9%) and emotional and social benefits (66.4%). Conclusion: We conclude that most of the study participants were satisfied with their results. Unfortunately, there is a lack of data in Saudi Arabia, and this study somewhat fulfill the current gap about the advantages and disadvantages of AP surgery.